Influence of Acculturation Strategies on the Judgment of a Violent Act Committed by a North African Woman. Issue 1 (20th April 2018) - Dougez, Chloé; Taillandier-Schmitt, Anne; Combalbert, Nicolas
The aim of this research was to examine how judgment of an aggressive act committed by a North African immigrant woman was influenced by the perpetrator's acculturation strategies and the participants' level of social dominance orientation (SDO). Two hundred seven students read a scenario describing a physical assault committed by a North African woman. She was described as having one of four acculturation profiles (assimilation, integration, separation, and marginalization). The consequences of the assault were manipulated (low impact vs. high impact). Participants judged both the act and its perpetrator on different dimensions. When the aggressor had not adopted French culture and/or had maintained her original culture, the offense was explained by internal causes and was judged more severely, and the offender was judged more negatively and was perceived as having more masculine characteristics than in the other conditions. These results were particularly true for participants with a high level of SDO. SDO level also affected how participants rated the feminine characteristics of the offender. The acculturation strategy adopted by the aggressor as a factor not directly related to the act and SDO level played a crucial role in the way participants judged a North African woman carrying out a physical assault. The implications and issues of this study are discussed.